Post harvest evaluation and management of cherry Tomato[Solanum lycopersicum L.var.cerasiforme (Dunal) A.Gray] Genotypes - Rosemary M Xavier (Department of Processing Technology, College of Horticulture, 2017)
The present study entitled „Post harvest evaluation and management of cherry tomato [Solanum lycopersicum L. var. cerasiforme (Dunal) A. Gray] genotypes‟ was undertaken with the objectives of evaluating quality attributes of cherry tomato under rain shelter and open field conditions, and to standardise the packaging and storage requirements. Eleven genotypes of cherry tomato raised inside rain shelter and in open field were evaluated for the quality attributes. The physico-morphological characters showed significant variation among the cherry tomato accessions inside rain shelter. The desirable attributes like high fruit length, diameter, fruit girth, rind thickness, fruit weight, and juice per cent were observed for SLc.11, under both growing conditions. Performance of most of the genotypes was superior inside the rain shelter as compared to open field condition. The highest content of TSS, reducing and total sugar, vitamin C, total carotenoids and lycopene was observed in SLc.2 grown inside rain shelter. TSS, sugars and vitamin C content was higher for most of the genotypes under open field condition. Total carotenoids and lycopene content was higher for most of the genotypes when raised inside rain shelter. Packaging and storage studies were conducted in fruits of two genotypes, SLc.10 (small fruited type) and SLc.11 (large fruited type) by subjecting to four methods of packaging viz. packing in micro ventilated polyethylene cover (200 gauge), polystyrene tray covered with cling film, polypropylene punnets and shrink wrapping in polystyrene tray. Each package was stored in ambient (28 -36°C), refrigerated (5 ± 2°C) and cold storage (12 ± 3°C) conditions. The shelf life of cherry tomato was longer under cold storage than ambient and refrigerated condition. The shelf life of cherry tomato was extended to 87 days for IIHR- 2871 and 71 days for Pusa Cherry Tomato -1 under cold storage. Fruits packed in polypropylene punnets had longer shelf life for both varieties under refrigeration and cold storage conditions. The physiological loss in weight (PLW %) was significantly higher and shelf life was lower in unwrapped fruits under the three different storage conditions. The highest content of TSS, vitamin C, and lycopene was observed at different storage periods under three different storage conditions, because of the difference in the rate of ripening in these conditions. A trend of decrease in TSS, Vitamin C and lycopene content was recorded for majority of the treatments after reaching a peak value. TSS, Vitamin C and lycopene content was comparatively higher for fruits packed in polypropylene punnets, shrink wrapped fruits in polystyrene tray and fruits in polystyrene tray overwrapped with cling film respectively under the three storage conditions. In both the varieties, titrable acidity decreased as the ripening progressed during the storage. Significant changes in the titrable acidity was found in ambient storage of fruits. Total, reducing and non reducing sugars increased after one week of storage in all the treatments in both the varieties. Microbial load of cherry tomato was analyzed by estimating the population of bacteria, yeast, and fungi. Microbial load was found to increase with the advancement of storage period. Less microbial contamination was observed for samples kept under refrigeration. Organoleptic evaluation of both varieties revealed that the mean scores for all the attributes showed an increasing trend in the initial phase of storage and declined towards the end of the storage, but still the fruits were acceptable for consumption under ambient and cold storage.